Impresi Budaya Kerja Perusahaan Dalam Pengaplikasian Customer Relationship Management (CRM): Sebuah Tinjauan Literatur - Wijaya, Hery Derajad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
One form of business approach that is able to meet the demands of the times and technology related to all lines in achieving customer satisfaction is the application of Customer Relationship Management (CRM). On the other hand, the company's work culture has an influence or impact on company performance, which means that it also has an impact on customer service which certainly has an impression on the application of CRM. This article aims to examine the impression (influence) of corporate work culture on the application of CRM. The output of this publication is a unit of observation and explanation related to the influence of work culture in a company on the successful application of CRM. The method used is qualitative with a literature study approach with analysis techniques in the form of content analysis of selected articles which are then analyzed for observation units and their effects. The results show that the company's work culture in the form of customer orientation, collaboration and communication, innovation and continuous development, understanding and acceptance of data, and commitment to improving customer service, are important aspects in supporting the implementation of CRM.